Healing potentials of Marigold flower (Tagetes erecta) on full thickness dermal wound in caprine model - Sultana, Ajmary; Hasan, Mahadi; Rahman, Marzia; Alam, Md. Mahmudul (The European Research Journal, 2021)
Objectives: In the modern days multiple drug resistance has been developed against many microbes due to the random use of existing antimicrobial drugs in the treatment of infectious diseases. This paves the way for reconsidering traditional medicine; hence we have carried out to evaluate the wound healing potentials of Marigold flower (Tagetes erecta) in the surgical wound model in black Bengal goats. Methods: A total of sixteen surgical wounds were made in eight goats under proper restraint and analgesia. Wounds were topically treated with Marigold flower paste (Group A) and normal saline (Group B, control). Post-treatment information was recorded from day 1 to day 21. Planimetric features such as swelling of the wound area, elevation of suture line, and length of the wound were monitored. Histopathological and in vivo anti-microbial studies were also investigated. Results: Results revealed that aqueous paste of Tagetes erecta flower modulated inflammation and promoted wound contraction leading to earlier healing than those with saline. Histological findings highlighted the normal cutaneous architecture of the marigold treated wound more than that appeared in the saline-treated wound. The antibacterial study revealed that the aqueous paste of marigold flower was highly effective against Staphylococcus aureus which is the ubiquitous bacterial pathogen both in humans and animals. Conclusions: These results, thus, demonstrate that the aqueous paste of Tagetes erecta flower possesses wound healing activities and it could be a potential candidate for the treatment of dermal wounds by topical application.